TRAPPED POPULATIONS: MENANGANI PANDEMI COVID-19 UNTUK PENYINTAS BENCANA DI KOTA PALU - Abdul Fikri Angga Reksa (Research Centre for Population, Indonesian Institute of Sciences, 2020)
This article depicts the disaster survivors' recent situation amidst the COVID-19 crisis in Palu City (Central Sulawesi). Even though multiple disasters occurred around two years ago, there are still many people living in temporary shelters. They could not apply a health protocol recommendation such as physical distancing due to densely populated setting. Apart from that, they could not access a proper WASH facility in the evacuation camps. The coronavirus outbreak has been undermining the temporary shelters' dwellers hardly. Most of them are trapped or unable to move to a safe place, albeit they want to do it so. The local government has anticipated the worst-case scenario through direct assistance and stimulus programs. However, those ongoing programs are inadequate to reach the whole communities in need. In order to manage the COVID-19 pandemic, this article suggests people empowering approach by harnessing the existing social capital, for instance, social network and community-based initiatives. Learning from the tragedy on 28 September 2018, the community-based initiatives focus on providing basic needs (food, sanitizer, mask) and mental health support.Â